2014
DOI: 10.1111/joic.12142
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Oral Nicorandil Use in Diabetic Patients Undergoing Elective Percutaneous Coronary Intervention

Abstract: In diabetic patients undergoing elective PCI, nicorandil intake was associated with decreased incidence of PCI-related myocardial injury and improvement of LVEF% after 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 56 publications
(99 reference statements)
1
34
0
Order By: Relevance
“…The hidden distribution of the sixteen articles26272829303132333435363738394041 is low; Fifteen articles262728293031323334353637383941 used a random single blind method, but the blind method of one article40 is not clear. The incomplete outcome data, selective reporting of results and other biases of the sixteen articles26272829303132333435363738394041 are low. The literature quality score is shown in Table 2.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The hidden distribution of the sixteen articles26272829303132333435363738394041 is low; Fifteen articles262728293031323334353637383941 used a random single blind method, but the blind method of one article40 is not clear. The incomplete outcome data, selective reporting of results and other biases of the sixteen articles26272829303132333435363738394041 are low. The literature quality score is shown in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…Then, the full texts of 43 articles were downloaded to evaluate in detail. Eventually, data from 16 articles26272829303132333435363738394041 include 1616 patients were listed into this meta-analysis. Among these patients, 804 patients in the nicorandil group and 812 patients in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T heir conclusion that in diabetic patients undergoing elective PCI, intracoronary adenosine was associated with decreased incidence of PCIrelated myocardial injury and improvement of left ventricular EF % after 3 months despite there was no statistically significant difference between both groups regarding incidence of major adverse cardiac events (MACE). 27 Against our study , Chi-hang Lee et al In their study of 62 patients undergoing elective coronary angioplasty showed that pretreatment with intracoronary adenosine prevents the risk of periprocedural myocardial infarction. 28 In our current study the expected occurrence of periprocedural myonecrosis was absent, this may be potentially resulted from the low risk profile of our patients being not in acute coronary syndrome (ACS) sitting, our patients were patients with single vessel disease and not for complex PCI (e.g.…”
Section: Discussionmentioning
confidence: 64%